Mitigasi Resiko Investasi Bodong dan Aktualisasi Nalar Istiṣlāḥ - Arif, Firman Muhammad (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
This paper explores investments with manipulation and embezzlement. The reality of bulging investment development is considered to never die, even the number of victims and losses from year to year is increasingly fantastic in some areas. The fact of the rise in casualties and fantastic losses in the offense of the bulging investment is analyzed, elaborated, and formulated using the Istiṣlāḥ reasoning device as classical legal reasoning that is in line with regulations and is considered still relevant to the current context. This is a qualitative research that describes reality in society or is taken from a variety of sources that are minimal from manipulation and illusion so that the observations made are synergized with sensing or trusted. The results showed that efforts to minimize the impact of the rampant bulging investment were anticipated by the actualization of reasoning in both normative and empirical ways. The style of Istiṣlāḥ reasoning with its two segments namely maṣlaḥah mursalah and żarī’ah are collaborated with a legal or regulatory approach sourced from the government to degrade the fantastic number of victims to be drastic. Financial literacy education and law enforcement need to get primary attention.